PENGARUH MANAJEMEN LABA DAN GOOD CORPORATE GOVERNANCE TERHADAP KECURANGAN LAPORAN KEUANGAN - Oktaviani Kristina Kardhianti; Ceacilia Srimindarti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Fraudulent financial statements or material misstatements in financial statements, the highest incidence of fraud occurs, due to the weak system of good corporate governance in a company, weak good corporate governance, indicating the failure of financial statements to achieve their objectives to meet user information needs, where financial statements fail to present facts. real about the actual economic condition of the company. The purpose of this research is to examine and analyze the effect of earnings management and good corporate governance on mining subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses a population of all mining companies that have been listed on the Indonesia Stock Exchange (IDX) in the last five periods, namely 2016-2020, obtained a population of 190 companies. The sampling method used in this study was a purposive sampling technique with several selected criteria, so as to obtain a sample of 178 companies. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale, so it is called secondary data. Data collection techniques using documentation techniques. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that earnings management has a significant negative effect on financial statement fraud. Meanwhile, managerial ownership, the board of commissioners and the audit committee have no influence on fraudulent financial statements.